The Effect of Health Education Using the Emo-Demo Method on Parental Behavior in Meeting Children's Nutritional Needs - Usman Budi Antoro; Ro'isah; Marfuah (Health and Technology Journal (HTechJ), 2025)
The importance of adequate nutrition for children in supporting optimal growth and development and the role of health education in influencing parental behavior regarding this matter is well recognized. This study aims to evaluate the impact of health education using the Emo-Demo method on parental behavior in fulfilling children's nutritional needs at Posyandu Kenari, Lumajang Regency. The method used in this study is a pre-experimental design with a pre-test and post-test one-group design approach. The population and sample comprised 35 parent respondents who participated in the research. Data collection was conducted using a questionnaire, and the data were analyzed using the Wilcoxon test. The results showed that most respondents, 19 individuals (54.3%), exhibited poor behavior in fulfilling their children's nutritional needs before the intervention. After receiving health education using the Emo-Demo method, parental behavior improved significantly, with 25 individuals (71.4%) displaying good behavior. Statistical analysis using the Wilcoxon test showed a p-value of 0.000, indicating a significant effect of the health education intervention on changing parents' behavior. These findings highlight the importance of interactive and sustained health education approaches to support behavioral changes in a public health context. Therefore, structured health education programs using innovative methods like Emo-Demo can be more widely implemented to improve overall child health.